Prague 2016 Aplicant City (2008)
The task to promote the application process falls within the PRAGUE OLYMPIC Organisation's responsibility. The initial contract was signed on Thursday 22nd March by the Czech International Committee chairman Milan Jirásek and the Prague mayor Pavel Bém. Advisory board consists of Jan Winkler, Richard Mar(ík and Jir(í Kynos.